L’ardoise de couverture en Anjou au Moyen Âge et à l’époque moderne : l’exemple de la chapelle de la commanderie de Saulgé (Luigné, Maine-et-Loire) - Jean-Yves Hunot (Archéologie Médiévale)
The study method set up to study the ancient slates was applied to the remains discovered in the vault loins of the chapel at the commandery of Saulgé. This approach, based on the acquisition of dimensional and morphological characteristics, made it possible to describe these roofing slates both in their shape and in the way they were laid. This information led to the restoration of a thick slate roofing fixed to the nail with blurred joints and decreasing thickness. Based on this information, it was possible to estimate the quantity of material used at more than 13,000 slates with a weight of almost 10 tones. These elements of the modern period were compared with the results of other ensembles from Angevin contexts between the 11th and 16th centuries to be placed in a longer perspective. All of these ensembles highlight, over the entire period concerned, the preferential consumption of second-rate roofing slate within the production area and within a radius of around 50 kilometres, while the better-quality products (finer and regular) remained reserved for long-distance trade.